Alkyne–Azide Cycloadditions with Copper Powder in a High‐Pressure Continuous‐Flow Reactor: High‐Temperature Conditions versus the Role of Additives. Issue 4 (12th February 2013) - Ötvös, Sándor B.; Mándity, István M.; Kiss, Lóránd; Fülöp, Ferenc
Abstract A safe and efficient flow‐chemistry‐based procedure is presented for 1, 3‐dipolar cycloaddition reactions between organic azides and acetylenes. This simple and inexpensive technique eliminates the need for costly special apparatus and utilizes Cu powder as a plausible CuI source. To maximize the reaction rates, high‐pressure/high‐temperature conditions are utilized; alternatively, the harsh reaction conditions can be moderated at room temperature by the joint application of basic and acidic additives. A comparison of the performance of these two approaches in a series of model reactions has resulted in the formation of useful 1, 4‐disubstituted 1, 2, 3‐triazoles in excellent yields. The risks that are associated with the handling of azides are lowered, thanks to the benefits of flow processing, and gram‐scale production has been safely implemented. The synthetic capability of this continuous‐flow technique is demonstrated by the efficient syntheses of some highly functionalized derivatives of the antifungal cispentacin.